Exploring the Mechanism of Flavonoids Through Systematic Bioinformatics Analysis - Qiu, Tianyi; Wu, Dingfeng; Yang, LinLin; Ye, Hao; Wang, Qiming; Cao, Zhiwei; Tang, Kailin (Frontiers in Pharmacology, 2018)
Flavonoids are the largest class of plant polyphenols, with common structure of diphenylpropanes, consisting of two aromatic rings linked through three carbons and are abundant in both daily diets and medicinal plants. Fueled by the recognition of consuming flavonoids to get better health, researchers became interested in deciphering how flavonoids alter the human body functions. Here we took a systematic bioinformatics study on 679 flavonoid compounds and 481 corresponding targets. Multiple human diseases related pathways including cancers, neuro-disease, diabetes and infectious diseases were significantly regulated by flavonoids. Specific functions of each flavonoid subclass were further analyzed in both target and pathway level. Flavones and isoflavones were significantly enriched in multi-cancer related pathways, flavan-3-ols were found focusing on cellular processing and lymphocyte regulation, flavones preferred to act on cardiovascular related activities and isoflavones were closely related with cell multisystem disorders. Relationship between chemical constitution fragment and biological effects indicated that different side chain could significantly affect the biological functions of flavonoids subclasses. Results discovered in this paper will highlights the common and preference functions of flavonoids and their subclasses, which concerning their pharmacological and biological properties.